Aplikasi SiCekN Untuk Pengecekan Nilai Siswa SMP Tonasa 1 Kabupaten Pangkep - Khadijah; Sutamrin; Ahmad Zaki; Sahid (Jurnal Hasil-Hasil Pengabdian dan Pemberdayaan Masyarakat, 2023)
To apply an assessment, all assessment data must be able to be recorded properly and easily traced back so that students who need special attention can be easily found and acted upon immediately. To facilitate the recording and tracing of values, the use of technological media is indispensable, such as the use of applications in assessments. SMP Tonasa 1 Kabupaten Pangkep is one of the campus partners experiencing problems, namely not being able to utilize information system technology as a medium for accessing and analyzing student grades. The purpose of this Community Service activity (PkM) is to have a PkM product in the form of the SiCekN application for SMP Tonasa 1 Kabupaten Pangkep, and to be able to increase partners' knowledge and skills in using the learning assessment information system application. The method used is in the form of making a Value Checking Information System (SiCekN) application with good communication and discussion with partners so that the application is in accordance with partner needs, preparing a manual for using the application, and training in the use of the Value Checking Information System (SiCekN) application. The result obtained was the realization of the Value Checking Information System (SiCekN) application for SMP Tonasa 1 Kabupaten Pangkep. The use of the application has been tested, developed and used properly since 2019 until now in 2023. Teachers have responded positively to the ease of inputting grades and the ease of access to the intranet network so they don't have to gather in a certain place. The use of the application consists of steps for students who will check grades and steps for teachers to input value data into the application.